A digital ethnography of fan reaction to sponsorship termination. Issue 3 (27th May 2017) - Delia, Elizabeth B.
ABSTRACT: Research question: Scholars have paid little attention to consumer response to the termination of a sponsorship. The purpose of this study was to examine the reaction of fans of a professional cycling team to a sponsorship terminating, which ultimately led to the team disbanding. Research methods: The research purpose was pursued through digital ethnography (via message boards and weblog), examining the case of Basque professional cycling fans. Comments were analysed to understand fans' reaction to the 2013 cessation of Euskaltel-Euskadi, a Basque professional cycling team, after its sponsor, Euskaltel, exited the partnership. Results and findings: Fan reaction to Euskaltel ending its sponsorship was somewhat paradoxical, in that the terminated sponsorship ultimately led to the team disbanding, yet fans appeared to be appreciative of Euskaltel. They continued to celebrate the team's corporate sponsor colour as they mourned the end of Euskaltel-Euskadi and questioned the future of Basque cycling. This reaction is made more logical by understanding the long-term duration of the partnership, and how Euskaltel's support of the team for nearly two decades led to the intermeshing of the team and its sponsor, thus avoiding negative sentiment. Implications: This study makes a meaningful contribution to the sponsorship literature, particularly sponsorship termination. This study is one of the first to examine consumer response to sponsorship termination in a real-world setting, and suggests a potential legacy effect of long-term sponsorship, such that fan reaction to a long-term sponsorship terminating may not be negative, especially if fans understand the sponsor's contribution over time.